Impact of a rigid body against a finite elastic bar set on a rigid foundation - To, Nguyen Dang (Vietnam Journal of Mechanics, 1988)
The solutions of the impact problems of a rigid body against an elastic bar formerly are based on the classical longitudinal vibration theory of an elastic bar. In this paper, we based on the more precise theory to deal with the impact problem of a rigid body against a finite elastic bar set on a foundation.